Bookstores in Lithuania in 2013–2018: Less Physical Bookstores, Less Choice of Books - Gudinavičius, Arūnas (Knygotyra, 2020)
Despite various global and local economic crises, the shift of some readers to screen reading, growing online shopping habits, and the shorter time spent on reading books, physical bookstores are able to change and retain their customers. This research is a continuation of a 2013 study in order to capture the current situation and identify the changes that have taken place in Lithuanian physical bookstores over the past five years. During the research, the list of bookstores operating in Lithuania compiled in 2013 was updated and clarified, and an analysis of the collected data and comparison with the data of 2013 were performed. The results showed that from 2013 to 2018 the number of bookstores in Lithuania decreased by 18.8%, to 168 units. On average, the number of inhabitants per Lithuanian bookstore increased by 16.2% and reached 16,720 inhabitants per bookstore; the number of municipalities with no bookstores at all increased to 15 (9 in 2013). The largest Lithuanian bookstore networks remained the same: Vaga and Pegasas, which maintained almost the same number of bookstores – 33 bookstores at the end of 2018. The number of medium-sized bookstore networks decreased, and only one of the nine small bookstore networks (2–3 bookstores), which owned two bookstores in 2013, remained. Such changes show that the two major bookstore networks Vaga and Pegasas are strengthening their market position. Calculated by the number of bookstores, in 2018 they already ran 39% of the market. The range of available books in physical Lithuanian bookstores has decreased – from an average 9 thousand titles in 2013 up to 6 thousand titles in 2018. It seems that the 2004–2008 race between physical bookstores for the largest range of book titles in the past is now witnessing an increase in the choice of additional goods in bookstores, sometimes even exceeding their book sales. The decrease and change in the number and range of physical bookstores in Lithuania since 2008 was due to several reasons – from the economic crisis at that time, the continuing decline of the population to the decline of book reading habits, and the transition of some readers to on-screen reading and online shopping.